Between Life and Work: A review of Lisa Appignanesi and John Forrester's Freud's women and Janet Sayers' Mothering psychoanalysis. - Van Zyl, Susan (PINS-Psychology in Society, 2026)
Writing a combined review of Liza Appignanesi and John Forrester's Freud's women and Janet Sayers' Mothering psychoanalysis, two books which seem appropriately united by a common project, has turned out to be a task of a demanding and somewhat disconcerting kind. What is disconcerting about this task stems from the fact that despite their common ground - and the promise of an interesting comparison this brings - even on a first reading the two works turn out to be of such different levels and qualities that one is left wondering whether they are, in fact, comparable at all. Is Mothering psychoanalysis put at an unfair disadvantage from the start by being compared with a work of the sheer size, let alone stature, of Freud's women? After all, double reviews are inevitably competitive in some sense and it is only in fairy stories that David stands anything like a real chance against Goliath.